Shifts in Soil Microbial Community Composition, Function, and Co-occurrence Network of Phragmites australis in the Yellow River Delta - Zhu, Pengcheng; Yang, Shuren; Wu, Yuxin; Ru, Yuning; Yu, Xiaona; Wang, Lushan; Guo, Weihua (Frontiers in Microbiology, 2022)
Soil microorganisms play vital roles in regulating biogeochemical processes. The composition and function of the soil microbial community have been well studied, but little is known about the responses of bacterial and fungal communities to different habitats of the same plant, especially inter-kingdom co-occurrence patterns including bacteria and fungi. We used high-throughput sequencing to investigate the bacterial and fungal communities of five Phragmites australis habitats in the Yellow River Delta and constructed their inter-kingdom interaction network through network analysis. Results showed that richness did not significantly differ among habitats for the bacterial or fungal communities. The distribution of the soil bacterial community was significantly affected by soil physicochemical properties, whereas that of the fungal community was not affected. The main functions of bacteria and fungi were to participate in the degradation of organic matter and element cycling, both of which are significantly affected by the soil physicochemical properties. Network analysis revealed that bacteria and fungi participated in the formation of networks through positive interactions. The role of intra-kingdom interactions were more important than inter-kingdom interactions. Rare species acted as keystone taxa and play a critical role in maintaining the network structure, while NO3−–N likely played an important role in maintaining the network topological properties. Our findings provide insights into the inter-kingdom microbial co-occurrence network and response of the soil microbial community composition and function to different Phragmites australis habitats in coastal wetlands, which will deepen our insights into the microbial community assembly in coastal wetlands.